The Economic Situation of Sukapura Regency during the Reign of Raden Adipati Aria Wiratanuningrat - Shavab, Oka Agus Kurniawan; Yulifar, Leli; Supriatna, Nana; Mulyana, Agus (History Department, Semarang State University and Historian Society of Indonesia, 2023)
Tasikmalaya Regency, under the government of Raden Adipati Aria Wiratanuningrat, experienced significant developments in batik, woven and cloth, factory construction, market development, transportation, economic centers, and the development of cooperation. This development was also followed by challenges that must be passed because, at that time, Tasikmalaya Regency faced a situation due to the world depression from 1929-1937. The purpose of this study was to describe the economic crisis of Tasikmalaya Regency during the reign of Raden Adipati Aria Wiratanuningrat. The method used is the historical method, a systematic set of principles and rules intended to assist in collecting historical sources, assessing them critically, and presenting a synthesis of the results achieved. The results found in this study include that Raden Adipati Aria Wiratanuningrat was able to make the people of Tasikmalaya Regency not panic when facing the impact of the world depression from 1929-1937. He can also provide solutions so that the economic situation continues to develop in a world depression. One solution is to build cooperation so that the business followed by the community continues. Economic developments that can be seen are the industrial centers of batik, woven cloth, hats, and umbrellas. There is also an increase in the number of factories, a wholesale market, and means of transportation that can facilitate the mobilization of the community and entrepreneurs.Keywords: Sukapura Regency, Tasikmalaya Regency, Raden Adipati Aria Wiratanuningrat, Priangan RegentKabupaten Tasikmalaya di bawah pemerintahan Raden Adipati Aria Wiratanuningrat mengalami perkembangan yang cukup signifikan di bidang kerajinan batik, anyaman dan kain, pembangunan pabrik, pembangunan pasar, transportasi, sentra ekonomi, dan berkembangnya cooperation. Adapun perkembangan ini juga diikuti dengan tantangan yang harus dilaluinya karena pada masa itu Kabupaten Tasikmalaya menghadapi situasi akibat depresi dunia pada tahun 1929-1937. Tujuan dari penelitian ini adalah untuk mengetahui gambaran situasi perekonomian Kabupaten Tasikmalaya pada masa pemerintahan Raden Adipati Aria Wiratanuningrat. Metode yang digunakan adalah metode sejarah, yaitu seperangkat prinsip dan aturan yang sistematis yang dimaksudkan untuk membantu dalam pengumpulan sumber-sumber sejarah, menilainya secara kritis, dan menyajikan suatu sintesis hasil yang dicapai. Hasil yang ditemukan pada penelitian ini di antaranya adalah Raden Adipati Aria Wiratanuningrat mampu membuat masyarakat Kabupaten Tasikmalaya untuk tidak panik saat menghadapi dampak depresi dunia pada tahun 1929-1937. Dia juga mampu memberikan solusi agar situasi perekonomian tetap berkembang dalam keadaan depresi dunia. Salah satu solusinya adalah mengembangkan cooperation agar usaha yang diikuti oleh masyarakatnya tetap berjalan. Perkembangan perekonomian yang terlihat yaitu adanya sentra industri kerajinan batik, anyaman dan kain, topi, dan payung. Terdapat juga peningkatan jumlah pabrik, adanya pasar induk, alat transportasi yang dapat memfasilitasi mobilisasi masyarakat dan pengusaha.Kata Kunci: Kabupaten Sukapura, Kabupaten Tasikmalaya, Raden Adipati Aria Wiratanuningrat, Bupati Priangan